ABDOMINAL SACROCOLPOPEXY VS VAGINAL SACROSPINOUS LIGAMENT FIXATION FOR VAGINAL VAULT PROLAPSES: Sequential Repair of Bilateral Ingniolasty - Choudhry, Abeera; Shukr, Irfan; Choudhry, Humaira; Bangash, Naila; Jan, Shahida (Pakistan Armed Forces Medical Journal, 2009)
Objective: To compare the success rate and outcome of two operations for vaginal vault prolepses-Vaginal Sacrospinous Ligament Fixation (SSL) versus Abdominal Sacrocolpopexy (SCP).Study Design: Prospective randomized controlled trial.Place and Duration of Study: Department of Obstetrics and Gynaecology CMH Peshawar between Jan 99 to Sep 2003 and Department of Obstetrics and Gynaecology MH Rawalpindi between Sep 2003 to Feb 2008.Patients and Methods: Thirty Women were randomly allocated to either procedure. There were a total of 15 patients in either arm. Follow up was at 3 and 6 months.Results: Thirty women with vault prolapse were selected and out of these,   15 each were randomized to SSL and SCL. The mean age of women was 54 years (range 42 – 70), mean weight 68 Kg (range 50 – 95 Kg), the duration of surgery was longer for SCP (46.1 versus 75.3 min, (p